H-atom site exchange in an iridium trans-dihydrogen/hydride complex, trans-[Ir(H)(?2-H2)(iPr)4(POCOP)(DMAP)]+ - Agrawal, Nisha K.; Gayathridevi, S.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Dalton Transactions, 2023)
Treatment of trans-[Ir(H)(N)(2)((iPr)4)(POCOP)(DMAP)][BAr4f] (2) with H-2 (1 bar) under ambient conditions (298 K) results in the formation of a trans-[Ir(H)(?(2)-H-2)((iPr)4)(POCOP)(DMAP)][BAr4f] (3) complex. Complex 3 exhibits H-atom site exchange between the bound H-2 and the hydride ligands which are mutually trans to one another. A plausible mechanism of this exchange involves metal-ligand cooperativity as studied by computations.